Nanomaterial for Adjuvants Vaccine: Practical Applications and Prospects - Vy Anh Tran; Vien Vo; Vinh Quang Dang; Giang Ngoc Linh Vo; Ta Ngoc Don; Van Dat Doan; Van Thuan Le (Indonesian Journal of Chemistry, 2024)
Vaccines contain adjuvants to strengthen the immune responses of the receiver against pathogen infection or malignancy. A new generation of adjuvants is being developed to give more robust antigen-specific responses, specific types of immune responses, and a high margin of safety. By changing the physical and chemical properties of nanomaterials, it is possible to make antigen-delivery systems with high bioavailability, controlled and sustained release patterns, and the ability to target and image. Nanomaterials can modulate the immune system so that cellular and humoral immune responses more closely resemble those desired. The use of nanoparticles as adjuvants is believed to significantly improve the immunological outcomes of vaccination because of the combination of their immunomodulatory and delivery effects. In this review, we discuss the recent developments in new adjuvants using nanomaterials. Based on three main vaccines, the subunit, DNA, and RNA vaccines, the possible ways that nanomaterials change the immune responses caused by vaccines, such as a charge on the surface or a change to the surface, and how they affect the immunological results have been studied. This study aims to provide succinct information on the use of nanomaterials for COVID-19 vaccines and possible new applications.